An Industrial systems analysis and design study on Ashlar Industrial Corporation - Cajustin, Jason; Chua, Anna Marin; Salvatierra, Michelle Rae.; Soriano, Erick Jon. (Diliman, Quezon City College of Engineering, 2004)
Ashlar Industrial Corporation was established in 1990 to produce OROCAN, a brand of plastic products. The company specializes in plastic injection molding and produces products such as utility storage containers, food keepers, basins, pitchers, cooler jugs, and specialty plastic industrial and agricultural containers. Their main raw materials are High Density Polyethylene (HDP) and Polypropylene (PP). Formal definitions of mission and vision statements were proposed based on the company's want to continually provide their customers with quality products and maintain market leadership in all of the products that they sell. The company's best asset is its established brand names, namely, OROCAN and CAHA de ORO. Their other assets are established long-term relationship with major raw material suppliers, experience in the business, and technology of an automated feed machine. The company may tap the potential of expanding its market internationally as there is a growing demand for PE products in the ASEAN region. Furthermore, there is increasing use of plastic in the products that the company sells. Lastly, the company may use the potentials of its newly acquired production monitoring system to maximize the use of its resources. The company's growth is limited by its lack of machines as their production level is deemed inadequate. The company needs to expand in order to meet more of its customers demand. Moreover, the buying power of the Philippine Peso is decreasing as foreign exchange rates are not stable. The major raw materials that the company use are imported and oil-based, thus a sudden increase in the price of oil products bring a steeper increase in the price of the raw materials. Business strategies were identified to help the company move towards attainment of its goal. The company may opt to expand its market by making available its products. This problem may be addressed by utilizing the unused land in its newly acquired warehouse facility to help increase their capacity. The company may also opt to improve its production system to maintain the quality of the products that they sell. The brand names are known to be of good quality, so it is necessary to maintain the quality associated to OROCAN and CAHA de ORO. Several key problems areas were identified: (1) need for process improvement, (2) insufficient capacity, (3) maintaining value associated to the products, and (4) knowing the particular want of the customers. To address the key problem areas, the functional strategies identified were: (1) Process Controlling, (2) use appropriate Forecasting Technique, (3) improving Brand Equity, and (4) learning the principles of Quality Function Deployment (QFD). The recommendations will be able to bring to the company an increase in the market share of up to 75% for the pail products.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Ashlar Industrial Corporation; Plastics industry and trade; System design